Effect of Nonsurgical Periodontal Therapy on Metabolic Control and Systemic Inflammatory Markers in Patients of Type 2 Diabetes Mellitus with Stage III Periodontitis - Rajashri Abhay Kolte; Abhay Pandurang Kolte; Pranjali Vijaykumar Bawankar; Vinisha A Bajaj (Wolters Kluwer Medknow Publications, 2023)
Background: A reciprocal relationship is understood to exist between periodontal disease and type 2 diabetes mellitus (T2DM), and this intervention study aimed to evaluate the effects of nonsurgical periodontal therapy (NSPT) on metabolic control, systemic inflammation, and cytokines in patients of T2DM with Stage III periodontitis. Materials and Methods: Sixty patients of T2DM with Stage III periodontitis were divided equally into two groups: intervention group (IG) and control group. Clinical parameters such as bleeding on probing (BOP), probing pocket depth (PPD), and clinical attachment level (CAL) were recorded at baseline and 3 and 6 months, and the serum samples were collected and processed at baseline and 6 months following NSPT to evaluate fasting plasma glucose, Glycosylated hemoglobin (HbA1c), interleukin-10 (IL-10), tumor necrosis factor-α (TNF-α), and high-sensitivity capsule-reactive protein (hs-CRP). Results: The results indicated a significant improvement in clinical parameters of PPD and CAL 6 months after NSPT (P = 0.005) in both the groups. However, a significant decrease (P < 0.0001) in the TNF-α, hs-CRP, blood glucose, and HbA1c levels was seen after NSPT. On the other hand, an increase in anti-inflammatory cytokine IL-10 was observed after NSPT in the IG. The changes in the pretreatment and posttreatment levels of all clinical, biochemical, and metabolic parameters, were found to be significant in both the groups except BOP. Conclusion: NSPT effectively improves periodontal condition, systemic inflammatory status, and glycemic control in patients of T2DM with Stage III periodontitis and decreases hs-CRP levels.